Endocardial Radiofrequency Ablation vs. Septal Myectomy in Patients With Hypertrophic Obstructive Cardiomyopathy: A Systematic Review and Meta-Analysis - Jiang, Tao; Huang, Bingyu; Huo, Shengqi; Mageta, Lulu Monica; Guo, Junyi; Lv, Jiagao; Lin, Li (Frontiers in Surgery, 2022)
Background: Septal myectomy (SM) has been the gold standard therapy for most patients with hypertrophic obstructive cardiomyopathy (HOCM). Endocardial radiofrequency ablation of septal hypertrophy (ERASH) is a novel treatment for septal reduction. We aimed to assess efficacy and safety between two treatment strategies. Methods: We searched PubMed, Web of Science, Cochrane Library, and Embase databases to identify relevant studies published up to March 2021. Random-effect models were used to calculate standardized mean difference (SMD) and 95% confidence intervals (CI) for resting left ventricular outflow tract gradient and septal thickness. Results: Twenty-five studies are included in this review, eighteen studies for SM and seven studies for ERASH. During follow-up, there were significant reductions of the mean resting left ventricular outflow tract gradient in adults (SM groups: SMD= -3.03, 95% CI: -3.62 to -2.44; ERASH groups: SMD= -1.95, 95% CI: -2.45 to -1.45) and children (SM groups: SMD= -2.67, 95% CI: -3.21 to -2.12; ERASH groups: SMD= -2.37, 95% CI: -3.02 to -1.73) after the septal reduction therapies. For adults, SM groups contributed to more obvious reduction than ERASH groups in interventricular septal thickness (SM groups: SMD= -1.82, 95% CI: -2.29 to -1.34; ERASH groups: SMD= -0.43, 95% CI: -1.00 to 0.13). The improvement of the New York Heart Association class was similar in the two groups (SM groups: 46.4%; ERASH groups: 46.7%). The peri-procedural mortality in SM and ERASH were 1.1% and 1.8%, respectively. Conclusions: This systematic review suggests that SM is superior to ERASH in the treatment of HOCM. But for patients, who are at risk for open cardiac surgeries or prefer a less invasive approach, ERASH might be an optional approach.